Striking Balance: Social Assistance Policy, the Public Trust, and the Public Service - Rosevear, Evan (The Journal of Public Policy, Administration, and Law, 2009)
Abstract: This article argues that while the provision of social assistance is an accepted reality in Canada it is supported by a multiplicity of contrary arguments in the context of scarce resources. As such, it must be the prerogative of elected leaders to balance the direction and resourcing of its provision with competing policy goals. However, this does not imply a political carte blanche with regard to policy development. In addition to any judicial check on policy-making, public servants have an obligation to ensure that the elected decision-makers are adequately informed about the rights issues involved as well as the various policy options available. Moreover, public servants must ensure that all normative and potentially rights abrogating decisions are made openly, transparently and subject to the scrutiny of a public that has the tools and means to understand and analyse information and to express itself accordingly in the political arena.